Political Polarization and Marketing Strategies of Pesantren Alumni in the 2024 Presidential Election - Bahar, Moh. Syaeful; Harnadi, Dodik; Ali, Ahmad Khubby (Postgraduate Studies of UIN Sunan Ampel Surabaya, Indonesia, 2025)
This study investigates the political dynamics of pesantren alumni from three influential pesantrens in East Java’s region: Pesantren Nurul Jadid Probolinggo, Pesantren Sidogiri Pasuruan, and Pesantren Salafiyah Syafi’iyah Situbondo, with fieldwork conducted in Bondowoso and Jember. Focusing on the 2024 presidential election, this research explores two key issues: the emergence of polarization among alumni groups and their adoption of political marketing strategies. Using a qualitative approach, the study finds that polarization intensified in line with divergent political preferences among the founding families of the parent pesantren. This division occurred not only across alumni networks of different pesantren origins but also within alumni of the same alma mater. The findings also show that each alumni group employed political marketing principles, combining push and pull strategies, to mobilize support and strengthen voter engagement for their preferred presidential candidate.